Irrigation modeling in a pear orchard - Nagy, A.; J., Tamás; T., Fórián; J., Nyéki; M., Soltész; Z., Szabó (International Journal of Horticultural Science, 2010)
The pear has large water requirement, therefore the planting of high density and grass covered pear orchards are needed irrigation conditions in Hungary. Drip irrigation spread in the orchards is due to the 90–95% of water use efficiency. One of the key role of irrigation is the proper determination of evapotranspiration and crop coefficients. As there is a considerable lack of information for different crops or fruits the Penman-Monteith method is used for the estimation of evapotranspiration, using CROPWAT 8.0. The research field was the genetic collection of pear at Újfehértó, in Hungary, which is situated in Nyírség meso-region. Our aim was to establish drip irrigation at this site. Based on the results of CROPWAT irrigation model the mean amount of the total gross irrigation is between 230–270 mm, within 3 irrigation interval regarding climatic and rainfall data of the last 10 years. In 2009, due to heavy drought, the total gross irrigation was 355,4mm/year on sandy soil calculating with 45% total available water depletion in 5 irrigation interval. The sizing of the irrigation system was set to the maximum 0.55 l/s/ha, which is 6.3 l/tree/h. 6.3 l/tree/h can be carried out with a drip emitter having 16 mm wing lines diameter, 4 l/h water flow at 3 atm pressure.